Affective Ability Of Students In Implementing Distance Learning : Kemampuan Afektif Siswa Dalam Pelaksanaan Pembelajaran Jarak Jauh - Luthfiyah, Fakkah Muhsinah; Carlian, H. Yayan; Rohmah, Siti Khozanatu (Madrosatuna: Journal of Islamic Elementary School, 2021)
The Covid-19 pandemic that occurred at this time had an impact on the world of education, including the education systwm in Indonesia. Traditional and routine learning that emphasizes the interaction of teachers and students in the classroom and outside the classroom has shifted to distance learning, this of course has positive and negative impacts on students, but what is very visible is the negative impact that arises from students. That is seen from the declining affective abilities of students such as the lack of independence and responsibility of students in learning. This study aims to determine the implementation of distance learning, students’ affective abilities in distance learning. The research method used is a mix method with a concurrent embeded strategy, which combines data analysis and quantitative and qualitative approaches simultaneously, namely the primary approach is qualitative approach and a secondary quantitative approach. This research was conducted at MI Cokroaminoto Banyuresmi Garut with the main research subjects students and teachers, while the principal and parents of students as supporting subjects. This study found that the implementation of distance learning carried out at MI Cokroaminoto was offline and online, the affective abilities of MI Cokroaminoto students showed differences from before and after the pandemic. The affective ability of students in the implementation of distance learning shows the attitude of student discipline, student responsibility, student independence, and student interest and attention shows not well during the process of implementing distance learning.